Multifunctional Metasurfaces Based on Direct Nanoimprint of Titania Sol–Gel Coatings. Issue 10 (13th March 2019) - Checcucci, Simona; Bottein, Thomas; Gurioli, Massimo; Favre, Luc; Grosso, David; Abbarchi, Marco
Abstract: Dielectric Mie resonators are taking momentum in the last years thanks to their peculiar properties in light management at visible and near‐infrared frequencies. However, their full exploitation demands for cheap materials and versatile fabrication methods, extendible over large surfaces and potentially C‐MOS compatible. Here, a sol–gel deposition and nanoimprint lithography method is used to obtain titania‐based Mie resonators over large areas (several square millimeters), showing that this platform can potentially be exploited for light management with different devices. First, their use for structural colors and efficient band pass filters covering the visible spectrum is demonstrated. Then, exploiting sharp Fano resonances in reflection, their potential for refractive index sensing is addressed obtaining a figure of merit of ≈20. Finally, when placing the resonators on porous silica, a large and reversible color tuning can be produced as a result of water adsorption within the substrate porosity. These results open the path to titania sub‐micrometric structures for applications as a multifunctional metamaterial for smart windows, displays, and all‐optical sensing. Abstract : A sol–gel deposition and nanoimprint lithography method to implement titania‐based Mie resonators over large areas (square millimeters) is exploited. Their use for tunable structural colors, efficient band pass filters covering the visible spectrum, and their suitability for refractive index sensing are demonstrated. These results showcase the potential of titania sub‐micrometric structures for smart windows, displays, and all‐optical sensing.